The application of six sigma for process control analysis in the Malaysian poultry wastewater treatment - Mohamad, Effendi; Ishak, Anuar; Arep @ Ariff, Hambali (Polish Society of Ecological Engineering (PTIE), 2022)
In this paper, the researchers presented the process control analysis of a Poultry Wastewater (PWW) treatment plant that was designed to comply with the Environmental Quality (Industrial Effluent) Regulations, 2009. In this pilot case study, the researchers highlighted the fact that owing to the existing global environmental challenges, a Six Sigma approach needs to be used for developing a new technique that helps in optimising process capability and assesses the treatment reliability. This would allow the effective treatment of different pollutants like pH, BOD5, TSS, COD, O&G and NH3-N before their discharge into the environment. The researchers used several quality control process tools like the I-MR control charts, treatment process capability analysis and treatment reliability assessment in the study. After analysing the data, the researchers concluded that the plant could effectively treat NH3-N, as well as fairly decrease the pH, BOD5, and COD values, whereas it displayed low ability in treating TSS and O&G within the research period. The researchers noted that the process showed low reliability in the treatment of TSS and O&G, i.e., 88.6% and 29.8% respectively, led to the discharge of fine colloids in the effluent. This was attributed to problematic processes in the PWW treatment procedure, such as malfunction of the DAF unit process, ineffective physical-chemical treatment, and tertiary filtration breakdown. The researchers concluded that this PWW plant required additional control and design improvement so that it released a low concentration of toxic compounds in the effluent discharge, and complied with the standards. This research could be used as a reference for additional studies that aimed to improve the quality of the wastewater treatment processes.